Effect of Angelica sinensis Polysaccharides on Osteoarthritis In Vivo and In Vitro: A Possible Mechanism to Promote Proteoglycans Synthesis. (4th June 2013) - Qin, Jun; Liu, Yan-song; Liu, Jun; Li, Jing; Tan, Yang; Li, Xiao-jun; Magdalou, Jacques; Mei, Qi-bing; Wang, Hui; Chen, Liao-bin
Abstract : This study investigated the effect of Angelica sinensis polysaccharides (APS-3c) on rat osteoarthritis (OA) model in vivo and rat interleukin-1-beta- (IL-1 β -) stimulated chondrocytes in vitro . APS-3c was administrated into rat OA knee joints and had protective effects on rat OA cartilage in vivo . Primary rat articular chondrocytes were cotreated with APS-3c and IL-1 β    in vitro . 2~50  μ g/mL APS-3c had no effect on chondrocytes viability, whereas it increased the proteoglycans (PGs) synthesis inhibited by IL-1 β . Microarray analysis showed that the significant changes were concentrated in the genes which were involved in PGs synthesis. RT-PCR confirmed that treatment with APS-3c increased the mRNA expression of aggrecan and glycosyltransferases (GTs) inhibited by IL-1 β but did not affect the mRNA expression of matrix-degrading enzymes. These results indicate that APS-3c can improve PGs synthesis of chondrocytes on rat OA model in vivo and IL-1 β -stimulated chondrocytes in vitro, which is due to the promotion of the expression of aggrecan and GTs involved in PGs synthesis but not the inhibition of the expression of matrix-degrading enzymes. Our findings suggest the clinical relevance of APS-3c in the prospective of future alternative medical treatment for OA.